Future city - Read, Stephen; Rosemann, Jürgen; Eldijk, Job van (Spon Press, 2005)
This text focuses on cities as the dominant form of human settlement for the future, examining the transformation that is happening in urban connobations worldwide today. The last few decades have seen a rate of change and growth in cities that has never been seen before, resulting in giant metropoles with over twenty million inhabitants. This book tackles the causes of these changes, and looks at how the planning and design of cities can shape the urban future.